Academic Readiness and Its Impact on Medical Students’ Performance: A Critical Analysis in The Context of Covid-19 Pandemic - Firmansyah, Marindra; Putri, Amanita Dias Ezha; Anisa, Rizki; Risandiansyah, Rio (Universitas Gadjah Mada, 2024)
Background: Student academic achievement in the first semester tends to be low and will increase the following semester. Many factors, including academic readiness, can influence this. Students have a diverse academic readiness, whereas a higher level of academic readiness would result in higher academic achievement. Previous research stated several factors shaped academic achievement in offline learning; however, online learning needs further exploration.Aims: Researchers aimed to discover the factors of academic readiness that affect students' academic achievement in online learning models during the COVID-19 pandemic.Methods: This research is a descriptive-analytic observational study with a cross-sectional approach. All dimensions were measured using a validated Academic Readiness Questioner direct translation questionnaire and using secondary data. Partial Least Squares with Structural Equation Model techniques using the Smart-PLS version 3.0 application were employed for data analysis.Result: This study produced an excellent, robust model with a GoF value > 0.36. Path analysis shows that all O-samples are positive with t statistics > 1.97, so these factors significantly positively affect academic readiness, except for the reading behavior dimension. Academic achievement is influenced by academic readiness, with R2=15.4%.Conclusion: Students' academic readiness positively and significantly affects academic achievement. Student academic readiness during online learning is shaped by achievement motivation orientation, goal orientation, integrated support, learning efficacy, M-score, social and economic conditions, number of credits, and reading behavior.